Upaya Meningkatkan Hasil Belajar PAI Melalui Model Pembelajaran Think Pair Share - Saiful Ahyar (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This research is based on students who are passive in religious learning. Students are more silent and indifferent in following the lessons given by the teacher. The subjects in this study were Class IX Students of SMP Negeri 1 Tinggi Raja Asahan TP. 2020/2021. The results of the data analysis can be concluded that there is an increase in the ability of student learning outcomes starting from cycle I to cycle II. Where in the first cycle, 21 students completely reached the level of mastery of learning outcomes or the percentage score was 82.5%. In cycle II, the result was that 25 students or a percentage score of 87.5% completed achieving the level of completeness of learning outcomes. Based on the results of reflection, it can be concluded that using the TPS learning model in PAI lessons can improve student learning outcomes in Class IX at SMP Negeri 1 Tinggi Raja, both individually and classically.Keywords: asmaul husna; think pair share Abstak: Penelitian ini berlatarbelakang siswa yang pasif dalam pembelajaran agama. Siswa lebih banyak diam dan cuek dalam mengikuti pembelajaran yang diberikan oleh guru. Subjek dalam penelitian ini adalah Siswa Kelas IX SMP Negeri 1 Tinggi Raja Kabupaten Asahan TP. 2020/2021. Hasil analisis data dapat disimpulkan bahwa terdapat pening-katan kemampuan hasil belajar siswa mulai dari siklus I sampai dengan siklus II. Dimana pada siklus pertama, 21 orang siswa tuntas mencapai tingkat ketuntasan kemam-puan hasil belajar atau persentase skornya 82,5%. Pada siklus II didapat hasil bahwa 25 orang siswa atau persentase skor 87,5% tuntas mencapai tingkat ketuntasan kemampuan hasil belajar. Berdasarkan hasil refleksi dapat disimpulkan bahwa dengan menggunakan model pembelajaran TPS pada pelajaran PAI dapat meningkatkan hasil belajar siswa diKelas IX SMP Negeri 1 Tinggi Raja baik secara individual maupun klasikal.Kata kunci: asmaul husna; think pair share